Design of an array structure for carbon-based field-effect-transistor type gas sensors to accurately identify trace gas species - Zou, Qiaoqiao; Liu, Bin; Zhang, Yong (Journal of materials chemistry. A, Materials for energy and sustainability, 2023)
The accurate identification of trace gases has become an important subject in the field of environmental monitoring due to the ppb-level permissible upper limit of indoor harmful gases. However, there are two challenges in trace gas detection, namely, the signal caused by the gas sensor is weak due to the extremely low concentration of trace gas, and the response signal of the target gas may be interfered by other gases owing to the crossing-sensitivity of materials. Herein, a carbon-based field effect transistor (FET) gas sensor array based on multi-sensing gates is presented. Based on the intrinsic amplifying effect of the field effect transistor, the proposed carbon-based FET-type gas sensor unit can detect the weak signal generated by 80 ppb gas at room temperature. Through the construction of the carbon-based FET gas sensor array structure with multi-sensing gates, the correlations between multiple parameters and gas species and concentrations are established, so as to realize the purpose of identifying the single unknown gas with an accuracy of 97.51%. This work provides a new strategy to develop micro gas sensor chips for accurate detection of trace gases at room temperature. A carbon-based FET gas sensor with a noble metal nanoparticles/Co 3 O 4 composites sensing gate is proposed to detect trace gases as low to 80 ppb. A sensor array with different sensing gates is designed to achieve accurate recognition of gases.